BleeMACS: rationale and design of the study. Issue 10 (October 2016) - D'Ascenzo, Fabrizio; Abu-Assi, Emad; Raposeiras-Roubín, Sergio; Simao Henriques, José Paulo; Saucedo, Jorge; González-Juanatey, José Ramon; Wilton, Stephen B.; Kikkert, Wouter J.; Nuñez-Gil, Iván; Ariza-Sole, Albert; Song, Xiantao; Alexopoulos, Dimitrios; et al.
Abstract : Background: Bleeding events after an acute coronary syndrome have a negative impact on prognosis. Available risk scores are limited by suboptimal accuracy, prediction of only in-hospital events and absence of patients treated with new antiplatelet agents in the current era of widespread use of percutaneous coronary intervention. Design: The BleeMACS (Bleeding complications in a Multicenter registry of patients discharged after an Acute Coronary Syndrome) project is a multicenter investigator-initiated international retrospective registry that enrolled more than 15 000 patients discharged with a definitive diagnosis of acute coronary syndrome and treated with percutaneous revascularization. The primary end point is the incidence of major bleeding events requiring hospitalization and/or red cell transfusion concentrates within 1 year. An integer risk score for bleeding within the first year after hospital discharge will be developed from a multivariate competing-risks regression. Conclusion: The BleeMACS registry collaborative will allow development and validation of a risk score for prediction of major bleeding during follow-up for patients receiving contemporary therapies for acute coronary syndrome.